AGGRESSIVE SYNCHRONOUS PAPILLARY AND FOLLICULAR THYROID CARCINOMAS IN A PATIENT PRESENTING WITH HYPERTHYROIDISM FROM GRAVES’ DISEASE - Ren, Gerald Sng Gui; Tse, Sarah Tan Ying; Chen, Edwin Chew Jun; Mantoo, Sangeeta; Ling, Chng Chiaw (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE We report a case of an uncommonly aggressive presentation of the rare entity of synchronous papillary (PTC) and follicular thyroid carcinomas (FTC) in a 67-year-old female initially presenting with thyrotoxicosis from Graves’ disease. She was found to have 2 thyroid nodules with extensive intra-cardiac tumour thrombus, symptomatic left pelvis bony metastasis with pathological fracture, pulmonary metastases, and mediastinal lymph node metastases. Further investigations suggested a diagnosis of synchronous papillary and metastatic follicular thyroid cancer. Treatment with radical surgery followed by adjuvant therapeutic radioiodine ablation was proposed, but the patient declined all forms of cancer-specific therapy and elected solely a palliative approach to treatment.